Does insurance protect individuals from catastrophic payments for surgical care? An analysis of Ghana's National Health Insurance Scheme at Korle-Bu teaching Hospital - Juliet Okoroh; Doris Ottie-Boakye Sarpong; Samuel Essoun; Robert Riviello; Hobart Harris; Joel S. Weissman (BMC, 2020)
Abstract Background According to the World Health Organization, essential surgery should be recognized as an essential component of universal health coverage. In Ghana, insurance is associated with a reduction in maternal mortality and improved access to essential medications, but whether it eliminates financial barriers to surgery is unknown. This study tested the hypothesis that insurance protects surgical patients against financial catastrophe. Methods We interviewed patients admitted to the general surgery wards of Korle-Bu Teaching Hospital (KBTH) between February 1, 2017 - October 1, 2017 to obtain demographic data, income, occupation, household expenditures, and insurance status. Surgical diagnoses and procedures, procedural fees, and anesthesia fees incurred were collected through chart review. The data were collected on a Qualtrics platform and analyzed in STATA version 14.1. Fisher exact and Student T-tests were used to compare the insured and uninsured groups. Threshold for financial catastrophe was defined as health costs that exceeded 10% of household expenditures, 40% of non-food expenditures, or 20% of the individual's income. Results Among 196 enrolled patients, insured patients were slightly older [mean 49 years vs 40 years P < 0.05] and more of them were female [65% vs 41% p < 0.05]. Laparotomy (22.2%) was the most common surgical procedure for both groups. Depending on the definition, 58-87% of insured patients would face financial catastrophe, versus 83-98% of uninsured patients (all comparisons by definition were significant, p < .05). Conclusion This study-the first to evaluate the impact of insurance on financial risk protection for surgical patients in Ghana-found that although insured patients were less likely than uninsured to face financial catastrophe as a result of their surgery, more than half of insured surgical patients treated at KBTH were not protected from financial catastrophe under the Ghana's national health insurance scheme due to out-of-pocket payments. Government-specific strategies to increase the proportion of cost covered and to enroll the uninsured is crucial to achieving universal health coverage inclusive of surgical care. Trial registration Registered at www.clinical trials.gov identifier NCT03604458.